Effect of Moringa oleifera Leaf Decoction on Total Cholesterol Levels in Obese White Rats (Rattus norvegicus) - Nurul Fiqriyatul Islamiyah; Irmayanti Irmayanti; Ratih Natasha Maharani; Prema Hapsari Hidayati; Andi Alamanda Irwan (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Total cholesterol is an essential lipid component required for the formation of hormones, vitamin D, and bile acids. However, elevated cholesterol levels (>200 mg/dL) can lead to hypercholesterolemia and increase the risk of cardiovascular diseases. Besides pharmacological therapy such as simvastatin, which may cause side effects with long-term use, herbal alternatives are increasingly being explored. Moringa oleifera leaves contain phytochemicals with potential cholesterol-lowering effects. Objective: To determine the effect of Moringa oleifera leaf decoction on total cholesterol levels in male white rats (Rattus norvegicus). Methods: This study employed an experimental pretest–posttest control group design and was conducted from August to September 2025 at the Research Laboratory, Faculty of Medicine, University of Muslim Indonesia. Male white rats were divided into treatment groups receiving doses of 400 mg/kgBW and 800 mg/kgBW. Data were analyzed using the Paired Sample t-test and One-Way ANOVA. Results: All groups exhibited total cholesterol levels above normal prior to treatment. Administration of Moringa oleifera leaf decoction at doses of 400 mg/kgBW and 800 mg/kgBW significantly reduced total cholesterol levels (p = 0.000). The decoction significantly reduced cholesterol levels in obese rats, with efficacy comparable to simvastatin and no dose-dependent differences observed. Conclusion: Moringa oleifera leaf decoction has potential as an effective natural alternative for lowering total cholesterol levels in white rats.